Peak Rate of Run of from Watersheds of Soils Conservation Research Farm at Demotanr- Hazaribagh - Sriva, S.N. (Journal of Soil and Water Conservation, 2022)
The design of Soil Conservation Structures depends on the quantity of surface flow which is primarily influenced by hydrological parameters of the watershed, A number of such structures are to be installed in the newly started Soil Conservation Research Farm at Demotanr near Hazaribagh. Accordingly a study was made to assess the different types hydrological parameters in all four watersheds of the farm. Basin characteristics such as shape index, mean elevation average slope and important informations on Soil Survey were determined. The peak rate of run off for each drainage basin was separately assessed for hourly rainfall in 25 years frequency by the Rational method. There was no significant difference in the surface flow of the four drainage basins which may be due to similar watershed characteristics.